2006
DOI: 10.1093/rpd/ncl108
|View full text |Cite
|
Sign up to set email alerts
|

Usability of VTL from natural quartz grains for retrospective dosimetry

Abstract: To develop retrospective dosimetry of unexpected radiation accident, basic studies on violet thermoluminescence (VTL) phenomena were conducted using natural quartz grains. All VTL glowcurves of as-received samples did not exhibit peaks <250 degrees C, although for artificially irradiated quartz samples there were VTL peaks in the temperature region <250 degrees C. Therefore, accident doses could be estimated without the interference of naturally accumulated doses by VTL measurements from natural quartz. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…The dose profile was also estimated by VTL measurement. No natural signals of the VTL peak at 160 • C could be found in any of the VTL measurements as suggested in a previous paper (Fujita and Hashimoto, 2007). The results confirmed that the VTL dosimetry using the peak at 160 • C could evaluate, without background effects, the dose accumulated in a site affected by an accident.…”
Section: Depth Profile Of Naturally Accumulated Doses In Soil Using Ssupporting
confidence: 88%
“…The dose profile was also estimated by VTL measurement. No natural signals of the VTL peak at 160 • C could be found in any of the VTL measurements as suggested in a previous paper (Fujita and Hashimoto, 2007). The results confirmed that the VTL dosimetry using the peak at 160 • C could evaluate, without background effects, the dose accumulated in a site affected by an accident.…”
Section: Depth Profile Of Naturally Accumulated Doses In Soil Using Ssupporting
confidence: 88%
“…The MDL value is, for example, similar to that from violet TL dosimetry using quartz (Fujita and Hashimoto, 2007) and to that obtained using electron spin resonance dosimetry of saccharose (Kai et al, 1990).…”
Section: Minimum Detection Limitsupporting
confidence: 75%
“…The slices were gently crushed and chemically treated with 6 M HCl, 6 M NaOH and then 46% HF to extract quartz in the routine manner (e.g. Fujita and Hashimoto, 2007). From the remaining grains, coloured minerals were removed by hand picking.…”
Section: Methodsmentioning
confidence: 99%